“We are the soul, pearl and beauty of Hindu Kush Mountains”: exploring resilience and psychological wellbeing of Kalasha, an ethnic and religious minority group in Pakistan - Riaz, Fahad; Park, Miriam Sang-Ah; Golden, Karen Jennifer; Bokharey, Iram Zehra (Taylor and Francis Ltd., 2017)
The Kalasha are a marginalized ethnic and religious minority group in northern Pakistan. The Kalasha minority is known for their divergent polytheistic beliefs, and represents the outliers of the collectively monotheistic Muslim population of Pakistan. This study aimed to explore the psychological resilience beliefs and lived experiences of the Kalasha and to identify cultural protective factors and indigenous beliefs that help them maintain psychological wellbeing and resilience. Seven semi-structured interviews and two focus-group discussions were conducted. The total sample consisted of 6 women and 8 men, aged 20–58 years (Mage = 36.29, SD = 12.58). The Interpretative Phenomenological Analysis qualitative method was chosen. Study findings identified that factors contributing to the wellbeing, happiness and resilience enhancement beliefs of Kalasha included five main themes, all influenced by their unique spirituality: contentment, pride in social identity, tolerance, gender collaboration and gratitude. The study also revealed the Kalasha’s perception of their marginalization related to challenges and threats. The Kalasha emphasized bringing these resilience enhancement beliefs into practice, as a mean to buffer against challenges. In conclusion, this study revealed Kalasha’s wellbeing and resilience enhancement factors, which they believed in and practiced as an element of their indigenous culture and religion.